The role of tumor-associated fibroblast-derived exosomes in chemotherapy resistance of colorectal cancer and its application prospect - Liu, Meichen; Li, Teng-zheng; Xu, Congcong (Biochimica et biophysica acta. General subjects, 2025)
Colorectal cancer (CRC) is the second most common malignant tumor in the world. With its increasing incidence and younger age trend, its impact on human health has been paid more and more attention. Currently, we have a variety of chemotherapy drugs that can be used to treat colorectal cancer. However, the drug resistance of colorectal cancer has become a significant factor affecting its cure rate. Some studies have reported that exosomes are related to the occurrence of drug resistance. However, the exact mechanism is not precise. Therefore, we focused on the role of cancer associated-fibroblast-derived (CAFs-derived) exosomes in colorectal progression. It was found that cancer cells transmit information through exosome interaction and induce chemotherapy resistance by promoting epithelial-mesenchymal transition (EMT), up-regulating the Wnt/β-catenin signaling pathway, transforming growth factor-β1 (TGF-β1) pathway, promoting angiogenesis and other possible molecular mechanisms. In addition, in terms of clinical significance and therapeutic strategies, we explore the clinical relevance of CAFs-derived exosomes in colorectal cancer patients and their potential as potential biomarkers for predicting chemotherapy response. We also provide a new possible direction for overcoming chemotherapy resistance in colorectal cancer by targeting CAFs-derived exosomes. •The characteristics of CAFs-derived were described comprehensively.•The function of CAFs-derived in CRC was investigated.•The CAFs-derived as a potential target for the treatment of CRC was discussed.